Does self-ligating brackets type influence the hysteresis, activation and deactivation forces of superelastic NiTi archwires? - Rino Neto,José (2013)
OBJECTIVE: To compare hysteresis, activation and deactivation forces produced by first-order deformation of Contour 0.014-in NiTi wire (Aditek, Brazil) in four brands of self-ligating brackets: Damon MX, Easy Clip, Smart Clip and In-Ovation. METHODS: Activation and deactivation forces were measured in an Instron universal tensile machine at 3 mm/minute speed to a total displacement of 4 mm. Tests were repeated eight times for each bracket/wire combination. Statistical analysis comprised ANOVA and Tukey's multiple comparisons test. RESULTS: Using a 4-mm deformation, mean activation forces increased in the following order: Damon = 222 gf, Easy Clip = 228 gf, In-Ovation = 240 gf and Smart Clip = 306 gf. The same order was observed for mean hysteresis values, i.e., 128 gf, 140 gf, 150 gf and 206 gf, respectively. The respective values of deactivation forces for the Damon, Easy Clip, In-Ovation and Smart Clip brackets were 94 gf, 88 gf, 90 gf and 100 gf. CONCLUSIONS: Brackets with higher activation forces were accompanied by higher hysteresis values, which resulted in clinically similar deactivation forces, regardless of the type of self-ligating brackets used.